2004
DOI: 10.1097/01.ju.0000128572.31000.f0
|View full text |Cite
|
Sign up to set email alerts
|

Coronary Artery Risk Factors in Patients With Erectile Dysfunction

Abstract: Coronary artery risk factors are significantly associated with erectile dysfunction. A significant association between higher degrees of IHD and the increased severity of ED was detected.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
61
0
4

Year Published

2009
2009
2017
2017

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 92 publications
(65 citation statements)
references
References 17 publications
0
61
0
4
Order By: Relevance
“…1 It is now well documented that many risk factors for coronary artery disease (CAD), such as hypertension, smoking, dyslipidemia, diabetes mellitus (DM) and lack of physical exercise, are also risk factors for ED. 2,3 These shared risk factors contribute to endothelial dysfunction and impede the ability of the arteries to dilate, thereby inhibiting the occurrence of normal erection. In addition, a strong and independent correlation between ED and silent CAD had been reported in uncomplicated type 2 diabetic patients by Gazzaruso et al 4 The authors found a higher ED prevalence in uncomplicated type 2 diabetic patients with, than those without, silent myocardial ischemia (33.8 vs 4.7%, P ¼ 0.000).…”
Section: Introductionmentioning
confidence: 99%
“…1 It is now well documented that many risk factors for coronary artery disease (CAD), such as hypertension, smoking, dyslipidemia, diabetes mellitus (DM) and lack of physical exercise, are also risk factors for ED. 2,3 These shared risk factors contribute to endothelial dysfunction and impede the ability of the arteries to dilate, thereby inhibiting the occurrence of normal erection. In addition, a strong and independent correlation between ED and silent CAD had been reported in uncomplicated type 2 diabetic patients by Gazzaruso et al 4 The authors found a higher ED prevalence in uncomplicated type 2 diabetic patients with, than those without, silent myocardial ischemia (33.8 vs 4.7%, P ¼ 0.000).…”
Section: Introductionmentioning
confidence: 99%
“…Further, several epidemiological studies have demonstrated that ED is more prevalent among men with atherosclerotic diseases, including coronary artery disease (CAD), than it is in the general population. [3][4][5] It is now well established that many risk factors for CAD (hypertension, smoking, dyslipidemia, diabetes mellitus (DM) and lack of physical exercise) are also risk factors for ED; 6,7 at least one significant cardiovascular risk factor occurs in most ED patients. [8][9][10] This could be attributed to the fact that both CAD and ED are characterized by endothelial dysfunction and injury.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, in that study, it was also reported that severity (not prevalence) of ED was associated with severity of CAD. El-sakka et al [24] conducted a study on 417 male patients, of whom 27.6% had mild ED, 30% had moderate ED, and 42.4% had severe ED. They also indicated a correlation between coronary artery risk factors and ED and reported a significant correlation between ischemic heart disease and the increased severity and progressive course of ED.…”
Section: Discussionmentioning
confidence: 99%
“…Angiograms of the patients were scored and divided into three groups according to the SS as low (SS ≤22), intermediate (SS between [23][24][25][26][27][28][29][30][31][32], and high (SS ≥33) [8]. After coronary angiography, erectile performance statuses of all patients were evaluated using the International Index of Erectile Function (IIEF), which is a validated 15-item self-administered questionnaire [10].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation